mtROS Induced via TLR-2-SOCE Signaling Plays Proapoptotic and Bactericidal Role in Mycobacterium fortuitum-Infected Head Kidney Macrophages of Clarias gariepinus - Dahiya, Priyanka; Hussain, Md. Arafat; Mazumder, Shibnath (Frontiers in Immunology, 2021)
The mechanisms underlying Mycobacterium fortuitum-induced mycobacteriosis remain unexplored. Using head kidney macrophages (HKM) from catfish (Clarias gariepinus), we report that Ca2+ surge across mitochondrial-Ca2+ uniporter (MICU), and consequent mitochondrial ROS (mtROS) production, is imperative for mycobactericidal activity. Inhibition of mtROS alleviated HKM apoptosis and enhanced bacterial survival. Based on RNA interference (RNAi) and inhibitor studies, we demonstrate that the Toll-like receptor (TLR)-2–endoplasmic reticulum (ER) stress–store-operated calcium entry (SOCE) axis is instrumental for activating the mt-Ca2+/mtROS cascade in M. fortuitum-infected HKM. Additionally, pharmacological inhibition of mtROS attenuated the expression of CHOP, STIM1, and Orai1, which suggests a positive feedback loop between ER-stress-induced SOCE and mtROS production. Elevated tumor necrosis factor alpha (TNF-α) levels and caspase-8 activity were observed in HKM consequent to M. fortuitum infection, and our results implicate that mtROS is crucial in activating the TNF-mediated caspase-8 activation. Our results for the first time demonstrate mitochondria as an innate immune signaling center regulating mycobacteriosis in fish. We conclude that M. fortuitum-induced persistent SOCE signaling leads to mtROS production, which in turn activates the TNF-α/caspase-8 axis culminating in HKM apoptosis and bacterial clearance.